Evaluating Phillips curve based inflation forecasts in Europe: A note - Carsten Croonenbroeck; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2012)
We run out-of-sample forecasts for the inflation rate of 15 euro-zone countries using a NAIRU Phillips curve and a naïve reference model. Comparisons show that the naïve model returns better forecasts in almost all cases. We provide evidence that the Phillips curves' goodness of fit is rather high. However, forecasting power is comparatively low.
Keywords: C53; E31; E37; 330; Phillips Curve; Forecasting; Europe; RMSE